Binatang ama: Exploring the challenges confronting young fathers - Culasito, June Star M.; Pardillo, Rizza Mae A.; Payan, Remy Anne V. (Digos City ; UMDC, 2023)
Single young fathers are becoming more common in the Philippines, driven by a rise in pregnant teenagers and a scarcity of research on the dynamics and challenges of single fatherhood. Understanding the experiences, challenges, and coping strategies utilized by young, single fathers as they navigated parenthood was the main goal of the research questions. Using the Resilience and Schlossberg Transition theories, the study explores the experiences of young, single fathers. It was conducted in Davao del Sur, Philippines, involves six unmarried Filipino fathers aged 18-24. Utilizing purposive sampling and qualitative methods. Themes that emerged includes Accepting Fatherhood, Adjustments Due to Family s Initial Negation, and Asking Parental Support. The challenges identified encompass financial issues, work-study-life balance, dependency on parents, and unassisted child upbringing. Prioritizing childcare and support first, prioritizing employment before school, relying on parents, and setting an example for others are all examples of ways to cope. Participants showed maturity and preparedness for accepting parenthood responsibilities in spite of any challenges. There are implications for psychological practitioners as well as recommendations for further study concentrating on the unique requirements and difficulties faced by young single fathers, mental health, and the long-term effects on their kids. Keywords: single young father, fatherhood, dependency on parents, parenthood, childcare
Includes references and appendices.